2020
DOI: 10.1186/s12859-020-03844-4
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of enhancer–promoter interactions using the cross-cell type information and domain adversarial neural network

Abstract: Background Enhancer–promoter interactions (EPIs) play key roles in transcriptional regulation and disease progression. Although several computational methods have been developed to predict such interactions, their performances are not satisfactory when training and testing data from different cell lines. Currently, it is still unclear what extent a across cell line prediction can be made based on sequence-level information. Results I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 52 publications
1
23
0
2
Order By: Relevance
“…Moreover, EBF1, ZNF143, and RAD21 have a three-way interaction in GM12878 [ 56 ]. It is thus likely that the interaction of EBF1-ZNF143 may contribute to EP interactions [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, EBF1, ZNF143, and RAD21 have a three-way interaction in GM12878 [ 56 ]. It is thus likely that the interaction of EBF1-ZNF143 may contribute to EP interactions [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…With the transcription start sites (TSSs) defined in GENCODE, we defined 57,820 promoters, each of which was the genomic region from the upstream 1000 bps to the downstream of 100 bps the TSS of a GENCODE gene. An active promoter was then defined with these GENCODE promoters and the ENCODE RNA-seq data as previously [ 22 , 24 ]. In this way, every positive EP pair had its enhancer overlapping with one genomic region and its promoter overlapping with the other genomic region of a positive pair of genomic regions, and the distance between the active enhancer and the active promoter was within 2.5 kilobase pairs to 2 megabase pairs ( Supplementary S1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They obtained satisfactory prediction accuracy when train datasets were the same as test datasets, but performed worse across cell lines. Although EPIHC [ 23 ] and SEPT [ 24 ] both use different transfer learning approaches, their results are unsatisfactory.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies pointed out a new venue to explore the characteristics of EP interactions, which suggested that the interaction of transcription factors (TFs) that bind an enhancer and TFs that bind a promoter of an EP pair may contribute to the interaction of this EP pair [2,12,20,[27][28][29][30][31]. For instance, it is well known that the TF and structural protein CTCF binds to a fraction of enhancers and promoters, which facilitates the physical interaction of enhancers and promoters in these EP pairs [32].…”
Section: Introductionmentioning
confidence: 99%